The Use Of E-Portfolio To Improve Students’ Motivation And Attitudes Towards Learning English At University College Of Applied Sciences, Palestine - Shakfa, Mahmoud Dawoud (2018)
In the era of globalization and technological revolution, the widely spread usage of technology inside and outside of classrooms has encouraged educators and policymakers to look for new methods of assessment that suit the new digital generation. Therefore, the purpose of this study is to focus on four core issues; (1) to examine the outcome of using e-portfolio on the motivation of University College of Applied Sciences (UCAS) students' towards English language learning, (2) to investigate the outcome of using e-portfolio on UCAS students' attitudes towards English language learning, (3) to identify the benefits that the students are able to gain from utilizing e-portfolio among UCAS students' in an English Foreign Language (EFL) class, and (4) to identify problems in implementation of e-portfolio in UCAS students' EFL class. The total number of students in English Language social work classes under the humanitarian department at UCAS is 60 (30 males and 30 females). Those that are officially enrolling in English Language course (DIPL 1303) on the second semester of 2014/2015 academic year. A Sequential Exploratory Design was used to collect qualitative and quantitative data for a semester. The results of this study showed that instrumental and integrative motivation levels of UCAS students towards learning English after utilizing e-portfolio improving. The findings also revealed that the students’ attitude towards learning English changed positively after utilizing e-portfolio. Although the idea of e-portfolio is still fresh and not yet utilized in Palestine, it is essential to broaden the awareness of its benefits and challenges.